2007
DOI: 10.1016/j.febslet.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

PPARα‐dependent induction of the energy homeostasis‐regulating nuclear receptor NR1i3 (CAR) in rat hepatocytes: Potential role in starvation adaptation

Abstract: A tight hormonal control of energy homeostasis is of pivotal relevance for animals. Recent evidence suggests an involvement of the nuclear receptor NR1i3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…It has recently been shown that PPARa agonists lead to increased CAR expression via a PPRE (direct repeat 1, or DR1) in the CAR promoter (6). These same studies show that fasting-induced increases in free fatty acids (many of which are natural ligands for PPARa) induce CAR expression via PPARa activation.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…It has recently been shown that PPARa agonists lead to increased CAR expression via a PPRE (direct repeat 1, or DR1) in the CAR promoter (6). These same studies show that fasting-induced increases in free fatty acids (many of which are natural ligands for PPARa) induce CAR expression via PPARa activation.…”
mentioning
confidence: 59%
“…PPARa and CAR are induced in liver in response to fasting (6,7). It has recently been shown that PPARa agonists lead to increased CAR expression via a PPRE (direct repeat 1, or DR1) in the CAR promoter (6).…”
mentioning
confidence: 99%
“…Fastingdependent induction of CAR is mediated primarily by hepatocyte nuclear factor 4α (HNF4α) and PPARα [44,45] . Whereas fasted WT mice exhibit a higher CAR mRNA level compared with fed mice, this fasting response is almost completely attenuated in either HNF4α or PPARα knockout mice.…”
Section: Transcriptional Regulation Of Carmentioning
confidence: 99%
“…A species-dependent interaction was also observed among treatments with respect to gene regulation by the nuclear receptors CAR and PPAR. These changes may reflect species-dependent regulation of CAR responses after PPAR activation as discussed elsewhere (Guo et al, 2006;Wieneke et al, 2007;Saito et al, 2010;Rondini et al, 2016). In mouse hepatocytes, PPAR activation by the prototypical agonist Cipro decreased expression of the CAR target gene Fig.…”
Section: Regulation Of Hepatocellular Gene Expression By Isoprenoidsmentioning
confidence: 72%